Correlations between measures of ALS respiratory function: is there an alternative to FVC?. Issue 7 (2nd October 2021) - Murray, Deirdre; Rooney, James; Al-Chalabi, Amar; Bunte, Tommy; Chiwera, Theresa; Choudhury, Mutahhara; Chio, Adriano; Fenton, Lauren; Fortune, Jennifer; Maidment, Lindsay; Manera, Umberto; Mcdermott, Chris; et al.
Abstract: Background: An ongoing longitudinal study in six European sites includes a 3-monthly assessment of forced vital capacity (FVC), slow vital capacity (SVC), peak cough flow (PCF), and Sniff nasal inspiratory pressure (SNIP). The aim of this interim analysis was to assess the potential for SNIP to be a surrogate for aerosol generating procedures given COVID-19 related restrictions. Methods : This was a prospective observational study. Patients attending six study sites with King's Stage 2 or 3 ALS completed baseline FVC/SVC/SNIP/PCF and repeated assessments 3 monthly. Data were collected from March 2018 to March 2020, after which a COVID-19 related study suspension was imposed. Correlations between the measures were calculated. A Bayesian multiple outcomes random-effects model was constructed to investigate rates of decline across measures. Results : In total, 270 cases and 828 assessments were included (Mean age 65.2 ± 15.4 years; 32.6% Female; 60% Kings stage 2; 81.1% spinal onset). FVC and SVC were the most closely correlated outcomes (0.95). SNIP showed the least correlation with other metrics 0.53 (FVC), 0.54 (SVC), 0.60 (PCF). All four measures significantly declined over time. SNIP in the bulbar onset group showed the fastest rate of decline. Discussion : SNIP was not well correlated with FVC and SVC, probably because it examines a different aspect of respiratory function. Respiratory measures declined over time, but differentially according to the site of onset. SNIP is not a surrogate for FVC and SVC, but is a complementary measure, declining linearly and differentiating spinal and bulbar onset patients.